Laminar mixing of miscible fluids in a SMX mixer evaluated by magnetic resonance imaging (MRI). (1st December 2015) - Lim, Victor; Hobby, Alexander M.; McCarthy, Michael J.; McCarthy, Kathryn L.
Abstract: Inline mixing is an important unit operation in industrial processes. SMX mixers, which split, rotate and recombine flow, are considered the best static mixer for laminar mixing for a wide range of fluid viscosities. The objective of this work was to characterize mixing within a 9-element SMX mixer for miscible liquids using magnetic resonance imaging (MRI). Both Newtonian and non-Newtonian fluids were evaluated through the acquisition of consecutive MR images that provided spatially localised data of the mixing of 2 equal volume fluids. These images were viewed qualitatively and quantitatively. Mixing indices as a function of axial positions indicated that mixing is more rapid for Newtonian fluids than the non-Newtonian fluid for 50–50 by volume mixing. Characterisation of mixing behaviour within the SMX mixer allows improved prediction of performance based on fluid properties, flow ratio and injection location. Highlights: MRI is a powerful experimental technique to evaluate mixing in SMX static mixer. Mixing behaviour of different fluids can be discriminated by MR imaging. Shear thinning fluid exhibited slower rate of mixing under experimental conditions.